Tetanus: A Potential Public Health Threat in Times of Disaster. Issue 3 (20th February 2017) - Finkelstein, Paige; Teisch, Laura; Allen, Casey J.; Ruiz, Gabriel
Abstract: Background: Tetanus is a potentially fatal condition that is rare in urban environments but is seen in developing countries and post-natural-disaster. Therefore, the purpose of this report was to review the epidemiology, pathogenesis, and management of tetanus in the trauma patient. Methods: A thorough literature review was conducted to look for the most current and thorough guidelines on the prophylaxis and treatment of tetanus. PUBMED (National Center for Biotechnology Information, National Institutes of Health; Bethesda, Maryland USA), MEDLINE (US National Library of Medicine, National Institutes of Health; Bethesda, Maryland USA), and Cochrane Library (The Cochrane Collaboration; Oxford, United Kingdom) databases were searched for articles in English, published from 2005 to 2015, using the keywords "Tetanus, " "Trauma/Surgery, " and "Disaster." Controlled trials, randomized controlled trials, trials of adult patients, published guidelines, expert opinions, and review articles were selected and extracted. Results: Current vaccination schedules in developed countries provide prophylaxis for tetanus. However, when severe natural disasters occur, many patients may not be able to provide a reliable vaccination history. In these situations, tetanus immune globulin (TIG) is indicated; if resources are not limited, both tetanus toxoid and TIG should be given to those with high-risk wounds. If resources are limited, TIG should be reserved for those that would benefit most or those least likely to have the protective antibodies. Conclusions: Although tetanus is a disease that has a low incidence in the developed world due to high rates of immunization, during large-scale natural disasters, compounding factors like the types of injuries, lack of medical services and supplies, and the delay in treatment associated with an already low immunization rate result in an increased incidence and outbreaks of the disease that has higher mortality in an underdeveloped society. It is important for the urban physician that cares for trauma and critical patients to become familiar with the protocols for treatment and immunization of patients that have tetanus-prone wounds, as well as recognize the potential for outbreaks in the settings of major natural disasters. P Finkelstein, L Teisch, CJ Allen, G Ruiz .Tetanus: a potential public health threat in times of disaster .Prehosp Disaster Med .2017 ;32 (3 ):339 –342 .